Accurate Diagnosis of Pseudomonas aeruginosa Is Critical to Mitigating Development of Antibiotic Resistance - Hala I. Al-Daghistani; Lubna F. Abu-Niaaj; Sima Zein (Antibiotics)
Background: The accurate and rapid diagnosis of infections is critical for effective and timely treatment. Misdiagnosis often leads to the prescription of antibiotics not targeting the causing agent of infection and thus be the possible development of multidrug resistance. This collectively worsens the condition and might lead to unnecessary intervention or death. The abundance of Pseudomonas spp. in healthcare-settings and the environment may lead to the inaccurate diagnosis of P. aeruginosa, making the treatment of its infections challenging. P. aeruginosa is a Gram-negative, opportunistic pathogen commonly linked to healthcare-associated infections. Its pathogenicity is attributed to several virulence factors correlated to enhanced survivability and colonization, invasion of the host tissues, and the development of multidrug resistance. When advanced diagnostic facilities are limited or unaffordable, the prescription of antibiotics solely relies on identifying the bacteria by culture-based methods. Objectives: This study aims to validate the accuracy of diagnosis of fifty clinical isolates preidentified as P. aeruginosa in three healthcare facilities in Jordan. Methods: The isolates were from infected areas of patients, including skin, wounds, ears, urine, and peritoneal cavities. Morphological and biochemical tests were performed, and the validation relied on the polymerase chain reaction (PCR) amplification of the 16S ribosomal ribonucleic acid (rRNA) gene. This molecular method is affordable for medical facilities with limited finances in contrast to advanced high-cost techniques. Results: The PCR confirmed that only 60% of the isolates were P. aeruginosa. All the confirmed isolates could produce different pigments and form biofilms. Conclusions: The high percentage of isolates mistakenly identified as P. aeruginosa raises concern about the suitability of prescribed antibiotics. The present study strongly recommends using advanced molecular methods to identify the pathogens. If conventional methods remain the only diagnostic option, this study recommends frequent external validation for tests in addition to performing an antibiotic susceptibility test to pinpoint the effective antibiotics against biofilm-producing P. aeruginosa.